Reverse Design: A current scientific vision from the international fashion and design congress - Broega, A. C. (2018)
The collaboration between the Textile Department of the University of Minho and the Brazilian Association of Studies and Research (ABEPEM) has led to an international platform for the exchange of research in the field of Fashion and Design: CIMODE. This platform is designed as a biennial congress that takes place in different European and Latin American countries with the co-organization of another university in each location. The current edition was jointly organized by the University of Minho and the Centro Superior de Diseño de Moda (CSDMM) - Universidad Politécnica de Madrid. CIMODE's mission is to explore fashion and design from a social, cultural, psychological and communication perspective, and to bring together different approaches and perceptions of practice, education and the culture of design and fashion. Through an interdisciplinary dialogue and intercultural perspective, CIMODE wants to generate and present new scenarios about the present and future of fashion and design. ‘DISEÑO AL REVÉS’ (‘BACKWARD DESIGN’) was the central theme of the 4th CIMODE (Madrid, Spain, 21-23 May 2018), which produced a highly topical and relevant number of academic publications presented in this book.